Pengaruh Self-Expressive Brand, Brand Tribe, Brand Love Terhadap Word Of Mouth - Fernandus, Erick (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
This research aims to understand better how a brand which perceived by an individual can effects his/her preferences, wording (word of mouth), and peer group(s). In case study, this research is using Apple brand because Apple brand has become the eye of the world and most trending topic on their product launching every year. And after its launching, there will be always reviews about its product. This research questions are examined through a set of questionnaires towards people who has Apple brand’s products. The findings of this study contribute to our current understanding of how our word of mouth towards effect one’s brand. The practical implications of this study suggest that brands should be always close to its market by making a better product which has the capability for consumer to express his or her self through a brand and by doing it, simultnously create consumer’s love toward a brand but not by supporting a group or tribe toward specific brand if they want to penetrate the market better and more efficiently.